(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: The aim of this study was to determine the effect of Pilates exercises on body composition and dynamic balance performance in sedentary women.Methods: The sample of the study was composed of 16 (n=8 test group, and n=8 control group) volunteer sedentary women in the age range of 21-44 who were living in Kırıkkale district of Turkey. The women in the test group participated in a 45-minute Pilates exercise program 3 days a week and for 8 weeks. The women in the control group continued their daily lives for the 8-week period. In determining the body composition of the participants, height measurements, circumference measurements, and Bioelectric Impedance Analysis (BIA) method were used; whereas in determining their dynamic balance performances, Y Balance Test was used. The measurements were applied to the participants in the test and control groups before and after the 8-week Pilates exercise program. The data obtained from the measurements were evaluated by using SPSS 25.0 statistical package program.Results: As a result of the statistical analyses, it was found that there was a significant difference in the body composition values and dynamic balance performance values of the women in the test group (p<0.05); while there was no significant difference in the values of the women in the control group (p>0.05).Conclusions: According to the findings obtained from the statistical analyses in the study, it was concluded that the 8-week Pilates exercise program contributed to the development of body composition and dynamic balance performance in sedentary women. For this reason, Pilates exercises can be recommended for sedentary women to be able to maintain their health and perform normal daily tasks that require the control of dynamic movements more easily.